Antimicrobial peptides as additives to beef cattle nutrition - Silveira, Raiza Felismino [UNESP] (2021)
Antimicrobial peptides (AMPs), identified in recent years from several species of vertebrate and invertebrate animals, have been receiving attention as a possible substitute for feed additives currently used for animals. One of these molecules, extracted from a frog from the Brazilian Cerrado, proved to be a promising antibiotic molecule due to its biological activity against fungi and bacteria. The Ctx(Ile21)-Ha peptide and its ent-Ctx(Ile21)-Ha isomer proved to be capable of permeabilizing and destroying bacterial membranes and, therefore, have become the focus of studies for the nutrition of beef cattle aiming at reducing of Gram-positive bacteria, since their unspecific mode of action (targets cell membranes) hinder the process of bacterial resistance. Aiming to evaluate the effects of the application of Ctx(Ile21)-Ha and its ent-Ctx(Ile21)-Ha isomer for beef cattle kept under grazing system in comparison with conventional additives used in animal feed, four in vitro studies were conducted with different substrates combined with monensin and virginiamycin additives and doses of antimicrobial peptides. pH, gas production, methane production, short-chain fatty acid profile and rate of dry matter and neutral detergent fiber disappearance were evaluated. AMPs reduced gas production. Methane production, in general, was significantly affected by the interaction between substrate and additive. Furthermore, the disappearance rate was not significantly affected by the use of AMPs. The production of short-chain fatty acids showed significant differences, with the acid profile in treatments with AMPs similar to those with monensin. Intermediate levels of AMP ent-Ctx(Ile21)-Ha showed a reduction in the emission of gases and methane, without compromising the use of dry matter and neutral detergent fiber, showing that the reduction of gases was not due to the reduction in use of nutrients by microorganisms. Complementary studies should be conducted to better understand the mode of action and effects of adding AMPs to ruminants’ diet.